2023
DOI: 10.3390/su15043378
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Coastal Landscape Pattern Index in the District of Nansha

Abstract: The regional ecological security and sustainable development are impacted by the changing terrain pattern. It is important to investigate the temporal and spatial shifts in coastal city landscape patterns As they have significant directing implications for coastal city landscape pattern improvement. The analytical results of the landscape pattern index of the coastal zone in the Nansha District of Guangzhou are investigated at three levels: patch level scale, type scale, and overall landscape scale, utilizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The similarity is that some scholars have studied the waterscape zone with a single method, rather than comprehensively. This is the limitation of current research and the direction that needs to be improved [48][49][50][51][52].…”
Section: Comparison With Existing Research Progressmentioning
confidence: 97%
“…The similarity is that some scholars have studied the waterscape zone with a single method, rather than comprehensively. This is the limitation of current research and the direction that needs to be improved [48][49][50][51][52].…”
Section: Comparison With Existing Research Progressmentioning
confidence: 97%
“…Sun et al [27] used the Markov model to associate the relationship between landscape indices and soil sand production and suggested that the landscape index could be an essential indicator to influence the soil erosion sand production process. However, due to the soil erosion process's complexity and the landscape index's limitations [28,29], selecting an appropriate landscape index will effectively advance the intrinsic association between changes in landscape patterns and soil erosion processes [30]. Furthermore, hydrodynamic characteristics are essential to reflect the soil erosion process on slopes and its kinetic mechanism [31].…”
Section: Introductionmentioning
confidence: 99%